Mildew-proof quick-drying towel fabric and preparation method thereof

The anti-mold fast-drying towel fabric prepared by electrospinning technology uses conjugated metal coordination connection and long-chain quaternary ammonium salt branching to solve the problem of bacteria growing in wet and low temperature environments, and achieves good anti-mold properties and quick-drying.

CN115012063BActive Publication Date: 2025-01-10高阳县凯强纺织品制造有限公司
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202210752922.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-06-28
Publication Date
2025-01-10
Estimated Expiration
2042-06-28

AI Technical Summary

Technical Problem

Towels are prone to breed bacteria in autumn and winter and plum rainy seasons due to the humid air and low temperatures, which lead to health hazards. The existing technology has not effectively solved the problems of mildew prevention and quick drying.

Method used

Polypropylene alcohol, modified conjugated porous polymer and modified copolymer were prepared by electrospinning technology, and the anti-molding towel fabric was improved through conjugated metal coordination connection and long-chain quaternary ammonium salt branching. performance.

Benefits of technology

It significantly improves the anti-mold, quick-drying and antibacterial durability of towels, ensuring rapid drying in low-temperature and humid environments and effectively preventing mold growth.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a kind of mildew-proof quick-drying towel fabric and its preparation method, and relates to the technical field of textile materials. When preparing mildew-proof quick-drying towel fabric, the present invention first reacts p-hydroxybenzaldehyde and cyanuric chloride to obtain a prepolymer, and reacts the prepolymer, 4,4'-diamino-2,2'-bipyridine, and 4,4'-diaminostilbene to obtain a conjugated porous polymer, and then reacts with ferric chloride, 4-hydroxypyridine, and 2,2-dimethylolpropionic acid in sequence to obtain a pre-modified conjugated porous polymer, and finally reacts with 10-undecylamine and iodomethane to obtain a modified conjugated porous polymer, p-aminostyrene and propylene are reacted to obtain a copolymer, and then reacts with 1,2,4,5-tetrakis (4-carboxyphenyl) benzene to obtain a modified copolymer, polypropylene alcohol, modified conjugated porous polymer, and modified copolymer are electrostatically spun into fibers, and fiber weaving is obtained to obtain mildew-proof quick-drying towel fabric. The mildew-proof quick-drying towel fabric prepared by the present invention has excellent mildew resistance, quick-drying property, and antibacterial persistence.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of textile materials, in particular to a mildew-proof quick-drying towel fabric and a preparation method thereof. Background Art

[0002] There are many types of towels, but they can generally be classified into bath towels, face towels, square towels, floor towels, and beach towels. Among them, square towels are a kind of cleaning product, characterized by square pure cotton textiles, fluffy terry, and soft texture. The method of use is to wet and wipe the skin to achieve the effect of removing stains, cleaning and cooling. Other towels are basically used to absorb moisture from the body, such as bath towels are used after bathing, and face towels are generally used to dry hands after washing. Floor towels are spread on the ground and stepped on after bathing to absorb moisture from the feet and prevent the feet from directly contacting the cold ground.

[0003] Towels are used every day in people's daily life, but in autumn and winter, they cannot be dried in time due to low temperature. In the rainy season, humid air and temperature can easily breed bacteria in towels, which is harmful to people's health. Such problems have not been solved, and it is necessary to invent a towel fabric with good mildew-proof and quick-drying properties to meet people's needs. Summary of the invention

[0004] The purpose of the present invention is to provide a mildew-proof quick-drying towel fabric and a preparation method thereof, so as to solve the problems existing in the prior art.

[0005] In order to solve the above technical problems, the present invention provides the following technical solutions:

[0006] A method for preparing a mildew-proof quick-drying towel fabric is characterized in that the mildew-proof quick-drying towel fabric is prepared by electrostatically spinning polypropylene alcohol, a modified conjugated porous polymer, and a modified copolymer into fibers, weaving the fibers into fabrics, and then cutting them.

[0007] As an optimization, the modified conjugated porous polymer is prepared by reacting p-hydroxybenzaldehyde and cyanuric chloride to obtain a prepolymer, and the prepolymer, 4,4'-diamino-2,2'-bipyridine, and 4,4'-diaminostilbene are reacted to obtain a conjugated porous polymer, which is then reacted with ferric chloride, 4-hydroxypyridine, and 2,2-dihydroxymethylpropionic acid in sequence to obtain a pre-modified conjugated porous polymer, and finally reacted with 10-undecenylamine and monoiodomethane to obtain the polymer.

[0008] As an optimization, the modified copolymer is prepared by reacting p-aminostyrene and propylene to obtain a copolymer, and then reacting the copolymer with 1,2,4,5-tetrakis(4-carboxyphenyl)benzene.

[0009] As an optimization, the preparation method of the mildew-proof quick-drying towel fabric includes the following preparation steps:

[0010] (1) Prepolymer, 4,4'-diamino-2,2'-bipyridine, 4,4'-diaminostilbene, o-dichlorobenzene, glacial acetic acid, and n-butanol are uniformly mixed in a mass ratio of 3:2:1:30:6:6 to 4:2:1:40:8:8, ultrasonicated at 20 to 30°C and 30 to 40kHz for 35 to 40 minutes, then placed in a high-pressure reactor with polytetrafluoroethylene as an inner liner, reacted at 80 to 90°C for 3 to 4 hours, the temperature was lowered to room temperature and then filtered, washed with ethyl acetate, tetrahydrofuran, and acetone for 3 to 5 times respectively, and dried at 60 to 70°C for 8 to 12 hours to obtain a conjugated porous polymer;

[0011] (2) 4-hydroxypyridine, the pretreated conjugated porous polymer, N,N-dimethylacetamide, anhydrous ethanol and pure water are mixed uniformly in a mass ratio of 1:8:50:50:10 to 1:10:60:60:15, ultrasonically treated at 50 to 60°C and 20 to 30kHz for 1 to 2 hours, filtered and washed with anhydrous ethanol for 3 to 5 times, dried at 60 to 70°C for 8 to 12 hours, and then placed in a vacuum impregnation machine, the pressure is reduced to 1 to 10Pa, and 4-hydroxypyridine is added. The pre-modified conjugated porous polymer is prepared by mixing an impregnation solution with a mass of 30 to 40 times that of pyridine, introducing nitrogen to a pressure of 10 to 20 kPa, standing at 10 to 20 ° C for 10 to 15 min, filtering and standing at 130 to 140 ° C for 1 to 2 h, and then placing in a vacuum impregnation machine to repeatedly impregnate with the impregnation solution, filtering and standing at 130 to 140 ° C for 2 to 3 h, washing with anhydrous ethanol for 3 to 5 times, and drying at 30 to 40 ° C, 5 to 8 Pa for 4 to 6 h to obtain a pre-modified conjugated porous polymer.

[0012] (3) 10-undeceneamine, pre-modified conjugated porous polymer, anhydrous ethanol and toluene were mixed uniformly in a mass ratio of 1:8:40:40 to 1:10:50:50, and a catalyst of 0.01 to 0.03 times the mass of 10-undeceneamine was added, and ultrasonic reaction was carried out at 60 to 70°C and 30 to 40 kHz for 6 to 8 hours. After cooling to room temperature, the mixture was filtered and washed with anhydrous ethanol for 3 to 5 times, and dried at -1 to -10°C and 1 to 10 Pa for 6 to 8 hours. h, then immersed in a monoiodomethane solution, stirred at 30-40°C and 500-800r / min for 4-6h, then heated to 50-60°C and maintained for 20-30min, cooled to 1-5°C and filtered, rinsed with 1-5°C 8% sodium bicarbonate solution for 3-5min, then washed with 1-5°C pure water for 3-5 times, dried at -10--1°C and 1-10Pa for 6-8h to obtain a modified conjugated porous polymer;

[0013] (4) The copolymer, 1,2,4,5-tetrakis(4-carboxyphenyl)benzene, N,N-dimethylacetamide, anhydrous ethanol and pure water are uniformly mixed in a mass ratio of 1:3:8:6:4 to 1:5:10:8:6, and then 0.02 to 0.03 times the mass of the copolymer of dicyclohexylcarbodiimide and 0.02 to 0.03 times the mass of the copolymer of 1-hydroxybenzotriazole are added, and the mixture is stirred at 40 to 50° C. and 500 to 800 r / min for 10 to 12 h, and then allowed to stand at 20 to 30° C. and 1 to 2 kPa for 6 to 8 h, filtered and washed with anhydrous ethanol for 3 to 5 times, and dried at -10 to -1° C. and 1 to 10 Pa for 6 to 8 h to obtain a modified copolymer;

[0014] (5) Polypropylene alcohol, modified conjugated porous polymer, modified copolymer, tetrahydrofuran, N,N-dimethylformamide, polyethylene glycol, and 50% ethanol by mass are mixed in a mass ratio of 3:1:1:6:6:0.1:4-5:1:1:8:8:0.2:5, and electrospun at a spinning voltage of 15-20 kV, a spinneret aperture of 0.7 mm, a receiving distance of 15-20 cm, an ambient temperature of 10-20° C., and allowed to stand at 50-60° C., 1-2 kPa for 4-6 hours to obtain fibers; the fibers are twisted to 70-90 D, and then formed into fibers with a gram weight of 80-90 g / m by a weaving machine. 2 Anti-mildew quick-drying towel fabric.

[0015] As an optimization, the preparation method of the prepolymer in step (1) is: p-hydroxybenzaldehyde, sodium hydroxide, water and acetone are mixed in a mass ratio of 3:1:10:10 to 5:2:15:15 to prepare a reaction liquid, and cyanuric chloride and acetone are mixed in a mass ratio of 1:60 to 1:70 to prepare a cyanuric chloride solution; the reaction liquid is placed in a nitrogen atmosphere, the reaction liquid is stirred at 20 to 30°C and 500 to 700 r / min, and 3 to 4 times the mass of the reaction liquid cyanuric chloride solution is added dropwise to the reaction liquid at a rate of 1.5 mL / min. After the addition is completed, the stirring reaction is continued for 2 to 3 hours, the temperature is raised to 50 to 56°C and the stirring reaction is continued for 3 to 5 hours, and then added into 0°C pure water and stirred at 500 to 700 r / min for 20 to 25 minutes, filtered and washed with pure water for 3 to 5 times, and dried at -10 to -1°C and 1 to 10 Pa for 6 to 8 hours to prepare the prepolymer.

[0016] As an optimization, the pretreatment method of step (2) is: the conjugated porous polymer and the ethanol solution with a mass fraction of 50-60% are mixed uniformly in a mass ratio of 1:8-1:10, ultrasonicated at 50-60°C and 20-30kHz for 1-2h, and then 0.8-1.2 times the mass of the conjugated porous polymer is added with ferric chloride, and the ultrasonication is continued for 40-50min, then cooled to 20-30°C, filtered, and washed with deionized water for 3-5 times, and dried at -10--1°C and 1-10Pa for 6-8h.

[0017] As an optimization, the impregnation solution in step (2) is prepared by uniformly mixing 2,2-dihydroxymethylpropionic acid and p-toluenesulfonic acid in a mass ratio of 100:1 to 100:2.

[0018] As an optimization, the catalyst in steps (3) and (4) is prepared by uniformly mixing triethylaluminum and titanium tetrachloride in a mass ratio of 1:1 to 3:5.

[0019] As an optimization, the preparation method of the copolymer in step (4) is: p-aminostyrene, propylene, anhydrous ethanol and toluene are uniformly mixed in a mass ratio of 1:1:6:6 to 1:1:8:8, and then a catalyst of 0.01 to 0.03 times the mass of p-aminostyrene is added, placed in a reaction kettle, reacted at 60 to 70°C for 6 to 8 hours, cooled to room temperature and then filtered, and washed with anhydrous ethanol for 3 to 5 times, and dried at -1 to -10°C and 1 to 10 Pa for 6 to 8 hours to prepare the copolymer.

[0020] Compared with the prior art, the beneficial effects achieved by the present invention are:

[0021] When preparing the mildew-proof quick-drying towel fabric, the present invention firstly reacts p-hydroxybenzaldehyde and cyanuric chloride to obtain a prepolymer, then reacts the prepolymer, 4,4'-diamino-2,2'-bipyridine and 4,4'-diaminostilbene to obtain a conjugated porous polymer, then reacts with ferric chloride, 4-hydroxypyridine and 2,2-dihydroxymethylpropionic acid in sequence to obtain a pre-modified conjugated porous polymer, finally reacts with 10-undecenylamine and iodomethane to obtain a modified conjugated porous polymer, electrospins polypropylene alcohol, the modified conjugated porous polymer and the modified copolymer into fibers, and weaves the fibers to obtain the mildew-proof quick-drying towel fabric.

[0022] First, 4-hydroxypyridine and the conjugated porous polymer form a conjugated metal coordination connection under the action of iron ions, and then react with 2,2-dihydroxymethylpropionic acid to branch and grow in the pores of the conjugated porous polymer to form terminal hydroxyl dendritic polyester. The conjugated porous polymer can convert light into electron migration, and the electron migration generates heat. The terminal hydroxyl dendritic polyester in the pores of the modified conjugated porous polymer forms a conduction channel for water molecules. The conjugated metal coordination connection improves the conduction of heat and conducts the heat to the conduction channel of adjacent water molecules, accelerating the conduction of water molecules, thereby improving the quick-drying property; the pre-modified conjugated porous polymer reacts with 10-undecenylamine and then reacts with iodomethane to form long-chain quaternary ammonium salt branches on the outside of the modified conjugated porous polymer. The long-chain quaternary ammonium salt branches are hydrolyzed into quaternary ammonium cations, which pierce the bacteria with their fat-soluble long carbon chains, eventually causing the bacteria to be inactivated, thereby improving the mildew resistance.

[0023] Secondly, p-aminostyrene and propylene are reacted to obtain a copolymer, which is then reacted with 1,2,4,5-tetrakis(4-carboxyphenyl)benzene to obtain a modified copolymer. The introduction of 1,2,4,5-tetrakis(4-carboxyphenyl)benzene increases the overall conjugated structure, improves the light-heat conversion conduction effect, and improves the quick-drying property. Secondly, the 1,2,4,5-tetrakis(4-carboxyphenyl)benzene side chains on the modified copolymer are hydrolyzed to form carboxyl anions, and the long-chain quaternary ammonium salt side chains on the modified conjugated porous polymer are hydrolyzed to form quaternary ammonium cations. The carboxyl anions and quaternary ammonium cations can be combined through electrostatic forces to reduce the loss and damage of the quaternary ammonium cations, thereby improving the antibacterial durability of the mildew-proof and quick-drying towel fabric. DETAILED DESCRIPTION

[0024] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0025] In order to more clearly illustrate the method provided by the present invention, the following examples are used to describe in detail the various index testing methods of the mildew-proof quick-drying towel fabrics prepared in the following examples are as follows:

[0026] Mildew resistance: The mildew-proof quick-drying towel fabrics obtained in each embodiment and the comparative example materials were taken with the same size, shape and thickness, and the antibacterial rate was determined according to the GB / T20944 standard method.

[0027] Quick-drying property: The mildew-proof quick-drying towel fabrics obtained in each embodiment and the comparative example material are taken with the same size, shape and thickness, immersed in water for a period of time under the same conditions, taken out, and then placed in the same low-temperature indoor environment and applied with the same light, and the drying time is recorded.

[0028] Antibacterial persistence: The mildew-proof quick-drying towel fabrics obtained in each embodiment and the comparative material are taken in the same size, shape and thickness, immersed in water under the same conditions, taken out and naturally air-dried, and repeated the same number of times. The antibacterial rate after use is determined according to the GB / T20944 standard method, and the retention rate is calculated as the antibacterial rate after use / initial antibacterial rate.

[0029] Example 1

[0030] A method for preparing a mildew-proof quick-drying towel fabric, the method for preparing the mildew-proof quick-drying towel fabric mainly comprises the following preparation steps:

[0031] (1) p-Hydroxybenzaldehyde, sodium hydroxide, water and acetone were mixed in a mass ratio of 3:1:10:10 to prepare a reaction solution, and cyanuric chloride and acetone were mixed in a mass ratio of 1:60 to prepare a cyanuric chloride solution; the reaction solution was placed in a nitrogen atmosphere, stirred at 20°C and 500 r / min, and cyanuric chloride solution 3 times the mass of the reaction solution was added dropwise to the reaction solution at a rate of 1.5 mL / min. After the addition was completed, the stirring reaction was continued for 2 hours, the temperature was raised to 50°C and the stirring reaction was continued for 3 hours, and then 0°C pure water was added and stirred at 500 r / min for 20 minutes. The prepolymer was filtered and washed with pure water for 5 times, and dried at -10°C and 1Pa for 8 hours to obtain a prepolymer; the prepolymer, 4,4'-diamino-2,2'-bipyridine, 4,4'-diaminostilbene, o-dichlorobenzene, glacial acetic acid, and n-butanol were mixed uniformly in a mass ratio of 3:2:1:30:6:6, and ultrasonicated at 20°C and 30kHz for 40 minutes, and then placed in a high-pressure reactor with polytetrafluoroethylene as an inner liner, reacted at 80°C for 4 hours, and the temperature was lowered to room temperature and filtered, and washed with ethyl acetate, tetrahydrofuran, and acetone for 3 times respectively, and dried at 60°C for 12 hours to obtain a conjugated porous polymer;

[0032] (2) 2,2-dihydroxymethylpropionic acid and p-toluenesulfonic acid were mixed in a mass ratio of 100:1 to prepare an impregnation solution; a conjugated porous polymer and a 50% ethanol solution were mixed in a mass ratio of 1:8, ultrasonicated at 50°C and 20kHz for 2h, and then 0.8 times the mass of the conjugated porous polymer was added with ferric chloride, and ultrasonicated for 40min. After that, the mixture was cooled to 20°C, filtered, and washed with deionized water for 3 times, and dried at -10°C and 1Pa for 8h to obtain a pretreated conjugated porous polymer; 4-hydroxypyridine, the pretreated conjugated porous polymer, N,N-dimethylacetamide, anhydrous ethanol and pure water were mixed. The mixture was mixed evenly in a mass ratio of 1:8:50:50:10, ultrasonicated at 50°C and 20kHz for 2h, filtered and washed with anhydrous ethanol for 3 times, dried at 60°C for 12h, placed in a vacuum impregnation machine, and the pressure was reduced to 1Pa, and then an impregnation solution with a mass of 30 times that of 4-hydroxypyridine was added, and nitrogen was introduced to make the pressure reach 10kPa, and the mixture was allowed to stand at 10°C for 15min, filtered and allowed to stand at 130°C for 2h, and placed in a vacuum impregnation machine again to be impregnated with the impregnation solution repeatedly, filtered and allowed to stand at 130°C for 3h, washed with anhydrous ethanol for 3 times, and dried at 30°C and 5Pa for 6h to obtain a pre-modified conjugated porous polymer;

[0033] (3) triethylaluminum and titanium tetrachloride were mixed in a mass ratio of 1:1 to prepare a catalyst; iodomethane, 8% sodium hydroxide solution and sodium iodide were mixed in a mass ratio of 5:3:0.003 to prepare an iodomethane solution; 10-undeceneamine, pre-modified conjugated porous polymer, anhydrous ethanol and toluene were mixed in a mass ratio of 1:8:40:40, and then 0.01 times the mass of 10-undeceneamine was added as a catalyst, and the mixture was heated at 60°C and 30kHz. Ultrasonic reaction for 8 hours, filtered after cooling to room temperature, washed with anhydrous ethanol 3 times, dried at -1°C, 1Pa for 8 hours, immersed in iodomethane solution, stirred at 30°C and 500r / min for 6 hours, heated to 50°C and kept for 30 minutes, cooled to 1°C and filtered, rinsed with 1°C 8% sodium bicarbonate solution for 5 minutes, washed with 1°C pure water 5 times, dried at -10°C, 1Pa for 8 hours, to obtain a modified conjugated porous polymer;

[0034] (4) triethylaluminum and titanium tetrachloride were mixed uniformly in a mass ratio of 1:1 to prepare a catalyst; p-aminostyrene, propylene, anhydrous ethanol and toluene were mixed uniformly in a mass ratio of 1:1:6:6, and then 0.01 times the mass of p-aminostyrene was added to the catalyst, placed in a reaction kettle, reacted at 60°C for 8 hours, cooled to room temperature, filtered, washed with anhydrous ethanol for 3 times, and dried at -1°C and 1 Pa for 8 hours to prepare a copolymer; the copolymer, 1,2,4,5-tetra(4 -carboxyphenyl)benzene, N,N-dimethylacetamide, anhydrous ethanol and pure water are mixed evenly in a mass ratio of 1:3:8:6:4, and then 0.02 times the mass of the copolymer of dicyclohexylcarbodiimide and 0.02 times the mass of the copolymer of 1-hydroxybenzotriazole are added, stirred at 40°C, 500r / min for 12h, and allowed to stand at 20°C, 1kPa for 8h, filtered and washed with anhydrous ethanol for 3 times, and dried at -10°C, 1Pa for 8h to obtain a modified copolymer;

[0035] (5) Polypropylene alcohol, modified conjugated porous polymer, modified copolymer, tetrahydrofuran, N,N-dimethylformamide, polyethylene glycol, and 50% ethanol by mass were mixed in a mass ratio of 3:1:1:6:6:0.1:4, and electrospun at a spinning voltage of 15 kV, a spinneret aperture of 0.7 mm, a receiving distance of 15 cm, an ambient temperature of 10°C, and allowed to stand at 50°C, 1 kPa for 4 h to obtain fibers; the fibers were twisted to 70D and then formed into fibers with a gram weight of 80 g / m by a weaving machine. 2 Anti-mildew quick-drying towel fabric.

[0036] Example 2

[0037] A method for preparing a mildew-proof quick-drying towel fabric, the method for preparing the mildew-proof quick-drying towel fabric mainly comprises the following preparation steps:

[0038] (1) p-Hydroxybenzaldehyde, sodium hydroxide, water and acetone were mixed in a mass ratio of 4:2:13:13 to prepare a reaction solution, and cyanuric chloride and acetone were mixed in a mass ratio of 1:65 to prepare a cyanuric chloride solution; the reaction solution was placed in a nitrogen atmosphere, stirred at 25°C and 600 r / min, and 3.5 times the mass of the reaction solution of cyanuric chloride solution was added dropwise to the reaction solution at a rate of 1.5 mL / min. After the addition was completed, the stirring reaction was continued for 2.5 hours, the temperature was raised to 53°C and the stirring reaction was continued for 4 hours, and then 0°C pure water was added and stirred at 600 r / min for 22 minutes. Filter and wash with pure water for 4 times, dry at -5°C and 5Pa for 7h to obtain a prepolymer; mix the prepolymer, 4,4'-diamino-2,2'-bipyridine, 4,4'-diaminostilbene, o-dichlorobenzene, glacial acetic acid and n-butanol in a mass ratio of 3:2:1:35:7:7, ultrasonicate at 25°C and 35kHz for 38min, place in a high-pressure reactor with polytetrafluoroethylene as the liner, react at 85°C for 3.5h, reduce the temperature to room temperature and filter, wash with ethyl acetate, tetrahydrofuran and acetone for 4 times respectively, dry at 65°C for 10h to obtain a conjugated porous polymer;

[0039] (2) 2,2-dihydroxymethylpropionic acid and p-toluenesulfonic acid were mixed in a mass ratio of 100:1.5 to prepare an impregnation solution; a conjugated porous polymer and a 55% ethanol solution were mixed in a mass ratio of 1:9, ultrasonicated at 55°C and 25kHz for 1.5h, and then ferric chloride (1 times the mass of the conjugated porous polymer) was added, and ultrasonicated for 45min. After that, the mixture was cooled to 25°C, filtered, and washed with deionized water for 4 times, and dried at -5°C and 5Pa for 7h to obtain a pretreated conjugated porous polymer; 4-hydroxypyridine, the pretreated conjugated porous polymer, N,N-dimethylacetamide, anhydrous ethanol and pure water were mixed in a mass ratio of 1:9. The mixture was uniformly mixed in a mass ratio of 1:9:55:55:12, ultrasonicated at 55°C and 25kHz for 1.5h, filtered and washed with anhydrous ethanol for 4 times, dried at 65°C for 10h, placed in a vacuum impregnation machine, and the pressure was pumped down to 5Pa, and then an impregnation solution with a mass of 35 times that of 4-hydroxypyridine was added, and nitrogen was introduced to make the pressure reach 15kPa, and allowed to stand at 15°C for 12min, filtered and allowed to stand at 135°C for 1.5h, and placed in a vacuum impregnation machine again to be impregnated with the impregnation solution repeatedly, filtered and allowed to stand at 135°C for 2.5h, washed with anhydrous ethanol for 4 times, and dried at 35°C and 7Pa for 5h to obtain a pre-modified conjugated porous polymer;

[0040] (3) triethylaluminum and titanium tetrachloride were mixed in a mass ratio of 2:3 to prepare a catalyst; iodomethane, a 9% sodium hydroxide solution and sodium iodide were mixed in a mass ratio of 5:3.5:0.004 to prepare an iodomethane solution; 10-undeceneamine, a pre-modified conjugated porous polymer, anhydrous ethanol and toluene were mixed in a mass ratio of 1:9:45:45, and a catalyst of 0.02 times the mass of 10-undeceneamine was added, and the mixture was heated at 65°C, 35K Hz ultrasonic reaction for 7h, filtered after cooling to room temperature, washed with anhydrous ethanol 4 times, dried at -5℃, 5Pa for 7h, immersed in iodomethane solution, stirred at 35℃ and 650r / min for reaction for 5h, heated to 55℃ and kept for 25min, cooled to 3℃ and filtered, rinsed with 3℃ 8% sodium bicarbonate solution for 4min, washed with 3℃ pure water 4 times, dried at -5℃, 5Pa for 7h, to obtain a modified conjugated porous polymer;

[0041] (4) triethylaluminum and titanium tetrachloride were mixed uniformly in a mass ratio of 2:3 to prepare a catalyst; p-aminostyrene, propylene, anhydrous ethanol and toluene were mixed uniformly in a mass ratio of 1:1:7:7, and then 0.02 times the mass of p-aminostyrene was added to the catalyst, placed in a reaction kettle, reacted at 65°C for 7 hours, cooled to room temperature, filtered, washed with anhydrous ethanol for 4 times, and dried at -5°C and 5 Pa for 7 hours to obtain a copolymer; the copolymer, 1,2,4,5-tetra(4-carboxylic acid) phenyl)benzene, N,N-dimethylacetamide, anhydrous ethanol and pure water are mixed evenly in a mass ratio of 1:4:9:7:5, and then 0.025 times the mass of the copolymer of dicyclohexylcarbodiimide and 0.025 times the mass of the copolymer of 1-hydroxybenzotriazole are added, stirred at 45°C and 600r / min for 11h, and allowed to stand at 25°C and 1.5kPa for 7h, filtered and washed with anhydrous ethanol for 4 times, and dried at -5°C and 5Pa for 7h to obtain a modified copolymer;

[0042] (5) Polypropylene alcohol, modified conjugated porous polymer, modified copolymer, tetrahydrofuran, N,N-dimethylformamide, polyethylene glycol, and 50% ethanol by mass were mixed in a mass ratio of 4:1:1:7:7:0.15:4.5, and electrospun at a spinning voltage of 18 kV, a spinneret aperture of 0.7 mm, a receiving distance of 18 cm, an ambient temperature of 15°C, and allowed to stand at 55°C, 1.5 kPa for 5 h to obtain fibers; the fibers were twisted to 80D and then formed into fibers with a gram weight of 85 g / m by a weaving machine. 2 Anti-mildew quick-drying towel fabric.

[0043] Example 3

[0044] A method for preparing a mildew-proof quick-drying towel fabric, the method for preparing the mildew-proof quick-drying towel fabric mainly comprises the following preparation steps:

[0045] (1) p-Hydroxybenzaldehyde, sodium hydroxide, water and acetone were mixed in a mass ratio of 5:2:15:15 to prepare a reaction solution, and cyanuric chloride and acetone were mixed in a mass ratio of 1:70 to prepare a cyanuric chloride solution; the reaction solution was placed in a nitrogen atmosphere, stirred at 30°C and 700 r / min, and cyanuric chloride solution 4 times the mass of the reaction solution was added dropwise to the reaction solution at a rate of 1.5 mL / min. After the addition was completed, the stirring reaction was continued for 2 hours, the temperature was raised to 56°C, the stirring reaction was continued for 5 hours, and then 0°C pure water was added and stirred at 700 r / min for 20 minutes. The prepolymer was filtered and washed with pure water for 5 times, and dried at -1°C and 10Pa for 6 hours to obtain a prepolymer; the prepolymer, 4,4'-diamino-2,2'-bipyridine, 4,4'-diaminostilbene, o-dichlorobenzene, glacial acetic acid, and n-butanol were mixed uniformly in a mass ratio of 4:2:1:40:8:8, and ultrasonicated at 30°C and 40kHz for 35 minutes, and then placed in a high-pressure reactor with polytetrafluoroethylene as an inner liner, reacted at 90°C for 3 hours, and the temperature was lowered to room temperature and filtered, and washed with ethyl acetate, tetrahydrofuran, and acetone for 5 times respectively, and dried at 70°C for 8 hours to obtain a conjugated porous polymer;

[0046] (2) 2,2-dihydroxymethylpropionic acid and p-toluenesulfonic acid were mixed in a mass ratio of 100:2 to prepare an impregnation solution; a conjugated porous polymer and a 60% ethanol solution were mixed in a mass ratio of 1:10, ultrasonicated at 60°C and 30kHz for 1 hour, and then 1.2 times the mass of the conjugated porous polymer was added with ferric chloride. After ultrasonication for 50 minutes, the mixture was cooled to 30°C, filtered, and washed with deionized water for 3 times, and dried at -1°C and 10Pa for 6 hours to obtain a pretreated conjugated porous polymer; 4-hydroxypyridine, the pretreated conjugated porous polymer, N,N-dimethylacetamide, anhydrous ethanol and pure water were mixed. The mixture was mixed evenly in a mass ratio of 1:10:60:60:15, ultrasonicated at 60°C and 30kHz for 1h, filtered and washed with anhydrous ethanol for 5 times, dried at 70°C for 8h, placed in a vacuum impregnation machine, the pressure was pumped down to 10Pa, and then an impregnation solution of 40 times the mass of 4-hydroxypyridine was added, and nitrogen was introduced to make the pressure reach 20kPa, and the mixture was allowed to stand at 20°C for 10min, filtered and allowed to stand at 140°C for 1h, and placed in a vacuum impregnation machine again to be impregnated with the impregnation solution repeatedly, filtered and allowed to stand at 140°C for 2h, washed with anhydrous ethanol for 5 times, and dried at 40°C and 8Pa for 4h to obtain a pre-modified conjugated porous polymer;

[0047] (3) triethylaluminum and titanium tetrachloride were mixed in a mass ratio of 3:5 to prepare a catalyst; iodomethane, sodium hydroxide solution with a mass fraction of 8-10% and sodium iodide were mixed in a mass ratio of 5:4:0.005 to prepare an iodomethane solution; 10-undeceneamine, pre-modified conjugated porous polymer, anhydrous ethanol and toluene were mixed in a mass ratio of 1:10:50:50, and then 0.03 times the mass of 10-undeceneamine was added as a catalyst, and the mixture was heated at 70°C and 40kH z Ultrasonic reaction for 6 hours, filtered after cooling to room temperature, washed with anhydrous ethanol 5 times, dried at -10℃, 10Pa for 6 hours, immersed in iodomethane solution, stirred at 800r / min at 40℃ for 4 hours, heated to 60℃ and kept for 20 minutes, cooled to 5℃ and filtered, rinsed with 5℃ 8% sodium bicarbonate solution for 3 minutes, washed with 5℃ pure water 3 times, dried at -1℃, 10Pa for 6 hours, to obtain a modified conjugated porous polymer;

[0048] (4) triethylaluminum and titanium tetrachloride were mixed uniformly in a mass ratio of 3:5 to prepare a catalyst; p-aminostyrene, propylene, anhydrous ethanol and toluene were mixed uniformly in a mass ratio of 1:1:8:8, and then 0.03 times the mass of p-aminostyrene was added to the catalyst, placed in a reaction kettle, reacted at 70°C for 6 hours, cooled to room temperature, filtered, washed with anhydrous ethanol for 5 times, and dried at -10°C and 10Pa for 6 hours to prepare a copolymer; the copolymer, 1,2,4,5-tetra(4 -carboxyphenyl)benzene, N,N-dimethylacetamide, anhydrous ethanol and pure water are mixed evenly in a mass ratio of 1:5:10:8:6, and then 0.03 times the mass of the copolymer of dicyclohexylcarbodiimide and 0.03 times the mass of the copolymer of 1-hydroxybenzotriazole are added, stirred at 50°C, 800r / min for 10h, and allowed to stand at 30°C, 2kPa for 6h, filtered and washed with anhydrous ethanol for 5 times, and dried at -1°C, 10Pa for 6h to obtain a modified copolymer;

[0049] (5) Polypropylene alcohol, modified conjugated porous polymer, modified copolymer, tetrahydrofuran, N,N-dimethylformamide, polyethylene glycol, and 50% ethanol by mass were mixed in a mass ratio of 5:1:1:8:8:0.2:5, and electrospun at a spinning voltage of 20 kV, a spinneret aperture of 0.7 mm, a receiving distance of 20 cm, an ambient temperature of 20°C, and allowed to stand at 60°C, 2 kPa for 4 h to obtain fibers; the fibers were twisted to 90D and then formed into fibers with a gram weight of 80 to 90 g / m by a weaving machine. 2 Anti-mildew quick-drying towel fabric.

[0050] Comparative Example 1

[0051] The preparation method of the mildew-proof quick-drying towel fabric of Comparative Example 1 is different from that of Example 2 only in that step (2) is not performed, and step (3) is modified as follows: triethylaluminum and titanium tetrachloride are mixed uniformly in a mass ratio of 2:3 to prepare a catalyst; iodomethane, a 9% sodium hydroxide solution and sodium iodide are mixed uniformly in a mass ratio of 5:3.5:0.004 to prepare an iodomethane solution; 10-undeceneamine, a conjugated porous polymer, anhydrous ethanol and toluene are mixed uniformly in a mass ratio of 1:9:45:45, and 10-undeceneamine is added. The catalyst with a mass of 0.02 times of the amine was subjected to ultrasonic reaction at 65°C and 35kHz for 7 hours, filtered after cooling to room temperature, washed with anhydrous ethanol 4 times, dried at -5°C and 5Pa for 7 hours, immersed in a monoiodomethane solution, stirred at 35°C and 650r / min for 5 hours, heated to 55°C and maintained for 25 minutes, cooled to 3°C and filtered, rinsed with 3°C sodium bicarbonate solution with a mass fraction of 8% for 4 minutes, washed with 3°C pure water 4 times, dried at -5°C and 5Pa for 7 hours, and a modified conjugated porous polymer was obtained. The remaining steps were the same as in Example 2.

[0052] Comparative Example 2

[0053] The preparation method of the mildew-proof quick-drying towel fabric of Comparative Example 2 is different from that of Example 2 only in that step (3) is not performed, and step (2) is modified as follows: 2,2-dihydroxymethylpropionic acid and p-toluenesulfonic acid are mixed uniformly in a mass ratio of 100:1.5 to prepare an impregnation solution; a conjugated porous polymer and a 55% ethanol solution are mixed uniformly in a mass ratio of 1:9, ultrasonicated at 55°C and 25kHz for 1.5h, and then 1 times the mass of the conjugated porous polymer is added with ferric chloride, and the ultrasonication is continued for 45min, then cooled to 25°C, filtered, and washed with deionized water 4 times, and dried at -5°C and 5Pa for 7h to obtain a pretreated conjugated porous polymer; 4-hydroxypyridine and the pretreated conjugated porous polymer are mixed uniformly. The compound, N,N-dimethylacetamide, anhydrous ethanol and pure water were mixed uniformly in a mass ratio of 1:9:55:55:12, ultrasonicated at 55°C and 25kHz for 1.5h, filtered and washed with anhydrous ethanol 4 times, dried at 65°C for 10h, placed in a vacuum impregnation machine, the pressure was pumped to 5Pa, and then an impregnation solution with a mass of 35 times that of 4-hydroxypyridine was added, and nitrogen was introduced to make the pressure reach 15kPa, and the mixture was allowed to stand at 15°C for 12min, filtered and allowed to stand at 135°C for 1.5h, placed in a vacuum impregnation machine again and impregnated with the impregnation solution repeatedly, filtered and allowed to stand at 135°C for 2.5h, washed with anhydrous ethanol 4 times, and dried at 35°C and 7Pa for 5h to obtain a modified conjugated porous polymer. The remaining steps were the same as in Example 2.

[0054] Comparative Example 3

[0055] The preparation method of the mildew-proof quick-drying towel fabric of Comparative Example 3 differs from that of Example 2 only in step (4), and step (4) is modified as follows: triethylaluminum and titanium tetrachloride are mixed uniformly in a mass ratio of 2:3 to prepare a catalyst. p-Aminostyrene, propylene, anhydrous ethanol and toluene are mixed uniformly in a mass ratio of 1:1:7:7, and then a catalyst of 0.02 times the mass of p-aminostyrene is added, placed in a reactor, reacted at 65°C for 7h, cooled to room temperature, filtered, washed with anhydrous ethanol 4 times, and dried at -5°C, 5Pa for 7h to obtain a modified copolymer. The remaining steps are the same as Example 2.

[0056] Comparative Example 4

[0057] The preparation method of the mildew-proof quick-drying towel fabric of Comparative Example 4 differs from that of Example 2 only in step (4), and step (4) is modified as follows: triethylaluminum and titanium tetrachloride are mixed uniformly in a mass ratio of 2:3 to prepare a catalyst; p-aminostyrene, propylene, anhydrous ethanol and toluene are mixed uniformly in a mass ratio of 1:1:7:7, and then 0.02 times the mass of p-aminostyrene is added to the catalyst, placed in a reactor, reacted at 65°C for 7h, cooled to room temperature, filtered, washed 4 times with anhydrous ethanol, and dried at -5°C, 5Pa The copolymer was dried for 7 hours to obtain a copolymer; the copolymer, butane tetracarboxylic acid, N, N-dimethylacetamide, anhydrous ethanol and pure water were mixed uniformly in a mass ratio of 1:4:9:7:5, and then 0.025 times the mass of the copolymer of dicyclohexylcarbodiimide and 0.025 times the mass of the copolymer of 1-hydroxybenzotriazole were added, stirred at 45°C, 600r / min for 11 hours, and allowed to stand at 25°C, 1.5kPa for 7 hours, filtered and washed with anhydrous ethanol for 4 times, and dried at -5°C, 5Pa for 7 hours to obtain a modified copolymer. The remaining steps were the same as in Example 2.

[0058] Comparative Example 5

[0059] The preparation method of the mildew-proof quick-drying towel fabric of comparative example 5 is different from that of embodiment 2 in that steps (1), (2) and (3) are not performed, and step (5) is modified as follows: polypropylene alcohol, modified copolymer, tetrahydrofuran, N,N-dimethylformamide, polyethylene glycol, and 50% ethanol by mass fraction are mixed uniformly in a mass ratio of 4:1:7:7:0.15:4.5, and electrospinning is performed, the spinning voltage is 18 kV, the spinneret aperture is 0.7 mm, the receiving distance is 18 cm, the ambient temperature is 15 ° C, and the fiber is allowed to stand at 55 ° C, 1.5 kPa for 5 hours to obtain the fiber; the fiber is twisted to 80D, and then formed into a fiber having a gram weight of 85 g / m 2 Anti-mildew quick-drying towel fabric.

[0060] Comparative Example 6

[0061] The preparation method of the mildew-proof quick-drying towel fabric of Comparative Example 6 is different from that of Example 2 in that step (4) is not performed, and step (5) is modified as follows: polypropylene alcohol, modified conjugated porous polymer, tetrahydrofuran, N,N-dimethylformamide, polyethylene glycol, and 50% ethanol by mass are mixed uniformly in a mass ratio of 4:1:7:7:0.15:4.5, and electrospinning is performed, the spinning voltage is 18 kV, the spinneret aperture is 0.7 mm, the receiving distance is 18 cm, the ambient temperature is 15 ° C, and the fiber is allowed to stand at 55 ° C, 1.5 kPa for 5 hours to obtain the fiber; the fiber is twisted to 80D, and then formed into a gram weight of 85 g / m 2 Anti-mildew quick-drying towel fabric.

[0062] Effect example

[0063] Table 1 below shows the performance analysis results of the mildew resistance, quick-drying property, and antibacterial durability of the mildew-proof and quick-drying towel fabrics of Examples 1 to 3 of the present invention and Comparative Examples 1 to 6.

[0064] Table 1

[0065] Antibacterial rate Drying time Retention rate Antibacterial rate Drying time Retention rate Example 1 99.3% 43min 96.1% Comparative Example 3 99.0% 57min 81.2% Example 2 99.5% 40min 96.2% Comparative Example 4 99.0% 55min 89.5% Example 3 99.6% 45min 95.8% Comparative Example 5 67.3% 89min 96.3% Comparative Example 1 99.1% 72min 95.7% Comparative Example 6 98.6% 60min 80.3% Comparative Example 2 84.7% 43min 95.3%

[0066] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 6 in Table 1, it can be found that the mildew-proof and quick-drying towel fabric prepared by the present invention has good mildew resistance, quick drying, and antibacterial durability.

[0067] From the comparison of the experimental data of Examples 1, 2, and 3 and Comparative Example 1, it can be found that the drying time of Examples 1, 2, and 3 is shorter than that of Comparative Example 1, which indicates that in the process of preparing the pre-modified conjugated porous polymer, 4-hydroxypyridine and the conjugated porous polymer form a conjugated metal coordination connection under the action of iron ions, and then react with 2,2-dihydroxymethylpropionic acid to branch and grow in the pores of the conjugated porous polymer to form a terminal hydroxyl branched polyester. The conjugated porous polymer can convert light into electron migration, which generates heat. The terminal hydroxyl branched polyester in the pores of the modified conjugated porous polymer forms a conduction channel for water molecules. The conjugated metal coordination connection improves the conduction of heat and conducts the heat to the conduction channels of adjacent water molecules, accelerating the water The conduction of molecules improves the quick-drying property of the mildew-proof quick-drying towel fabric; from the comparison of the experimental data of Examples 1, 2, 3 and Comparative Example 2, it can be found that the antibacterial rate of Examples 1, 2, and 3 is higher than that of Comparative Example 2, which shows that the pre-modified conjugated porous polymer reacts with 10-undecenylamine and then with iodomethane to obtain a modified conjugated porous polymer, and a long-chain quaternary ammonium salt branch is formed on the outside of the modified conjugated porous polymer. The long-chain quaternary ammonium salt branch is hydrolyzed into a quaternary ammonium cation, which pierces the bacteria with its fat-soluble long carbon chain, and finally causes the bacteria to be inactivated, thereby improving the mildew resistance of the mildew-proof quick-drying towel fabric; from the comparison of the experimental data of Examples 1, 2, 3 and Comparative Example 3, it can be found that the drying time of Examples 1, 2, and 3 is short compared with Comparative Example 3, and the durability rate is High, indicating that the copolymer prepared by the reaction of p-aminostyrene and propylene is reacted with an excess of 1,2,4,5-tetrakis(4-carboxyphenyl)benzene to obtain a modified copolymer. The introduction of 1,2,4,5-tetrakis(4-carboxyphenyl)benzene increases the overall conjugated structure, improves the light-heat conversion conduction effect, and improves the quick-drying property of the mildew-proof quick-drying towel fabric. Secondly, the 1,2,4,5-tetrakis(4-carboxyphenyl)benzene side chains on the modified copolymer are hydrolyzed to form carboxyl anions, and the long-chain quaternary ammonium salt side chains on the modified conjugated porous polymer are hydrolyzed to form quaternary ammonium cations. The carboxyl anions and quaternary ammonium cations can be combined by electrostatic force to reduce the loss and damage of the quaternary ammonium cations, thereby improving the antibacterial durability of the mildew-proof quick-drying towel fabric. ; From the comparison of the experimental data of Examples 1, 2, 3 and Comparative Example 4, it can be found that the drying time of Examples 1, 2, 3 is shorter than that of Comparative Example 4, and the durability is high, which shows that the use of 1,2,4,5-tetrakis(4-carboxyphenyl)benzene to modify the copolymer forms a relatively large 1,2,4,5-tetrakis(4-carboxyphenyl)benzene rigid closed branch on the copolymer side chain compared to the use of butanetetracarboxylic acid to modify the copolymer, and has a better protective effect on the long-chain quaternary ammonium salt branch on the modified conjugated porous polymer than butanetetracarboxylic acid, thereby improving the antibacterial durability of the mildew-proof quick-drying towel fabric. At the same time, water molecules control the opening and closing of the rigid closed branch chains, and the conjugated structure of the rigid closed branch chains can promote heat conduction, thereby improving the quick-drying property of the mildew-proof quick-drying towel fabric.

[0068] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.

Claims

1. A method for preparing a mildew-proof quick-drying towel fabric, characterized in that: The anti-mildew quick-drying towel fabric is prepared by electrospinning polypropylene alcohol, modified conjugated porous polymer, and modified copolymer into fibers, weaving the fibers into fabrics, and then cutting them. The specific preparation steps are as follows: (1) Prepolymer, 4,4'-diamino-2,2'-bipyridine, 4,4'-diaminostilbene, o-dichlorobenzene, glacial acetic acid and n-butanol are mixed uniformly in a mass ratio of 3:2:1:30:6:6-4:2:1:40:8:8, ultrasonically treated at 20-30°C and 30-40kHz for 35-40min, and then placed in a high-pressure reactor with polytetrafluoroethylene as an inner liner, reacted at 80-90°C for 3-4h, and filtered after the temperature was lowered to room temperature. The prepolymer is washed with ethyl acetate, tetrahydrofuran and acetone for 3-5 times respectively, and dried at 60-70°C for 8-12h to obtain a conjugated porous polymer. The preparation method of the prepolymer is as follows: p-hydroxybenzaldehyde, sodium hydroxide, water and acetone are mixed uniformly in a mass ratio of 3:1:10 : 10~5:2:15:15 are mixed evenly to prepare a reaction liquid, and cyanuric chloride and acetone are mixed evenly at a mass ratio of 1:60~1:70 to prepare a cyanuric chloride solution; the reaction liquid is placed in a nitrogen atmosphere, the reaction liquid is stirred at 20~30°C and 500~700r / min, and a cyanuric chloride solution of 3~4 times the mass of the reaction liquid is added dropwise to the reaction liquid at a speed of 1.5mL / min, and after the addition is completed, the stirring reaction is continued for 2~3h, the temperature is raised to 50~56°C and the stirring reaction is continued for 3~5h, and then added into 0°C pure water and stirred at 500~700r / min for 20~25min, filtered and washed with pure water for 3~5 times, and dried at -10~-1°C and 1~10Pa for 6~8h to prepare; (2) The conjugated porous polymer and 50-60% ethanol solution were mixed in a mass ratio of 1:8-1:10, and ultrasonicated at 50-60°C and 20-30kHz for 1-2h. Then, 0.8-1.2 times the mass of the conjugated porous polymer was added with ferric chloride, and ultrasonicated for 40-50min. After that, the mixture was cooled to 20-30°C, filtered, and washed with deionized water for 3-5 times. The mixture was dried at -10--1°C and 1-10Pa for 6-8h to obtain the pretreated conjugated porous polymer. 4-Hydroxypyridine, the pretreated conjugated porous polymer, N,N-dimethylacetamide, anhydrous ethanol and pure water were mixed in a mass ratio of 1:8:50:50:10-1:10:60:60:15, and ultrasonicated at 50-60°C and 20-30kHz for 1-2h. , filter and wash with anhydrous ethanol for 3 to 5 times, dry at 60 to 70°C for 8 to 12 hours, place in a vacuum impregnation machine, pump the pressure to 1 to 10Pa, add an impregnation solution of 30 to 40 times the mass of 4-hydroxypyridine, introduce nitrogen to make the pressure reach 10 to 20kPa, let stand at 10 to 20°C for 10 to 15 minutes, filter and let stand at 130 to 140°C for 1 to 2 hours, place in a vacuum impregnation machine again and impregnate with the impregnation solution repeatedly, filter and let stand at 130 to 140°C for 2 to 3 hours, wash with anhydrous ethanol for 3 to 5 times, dry at 30 to 40°C, 5 to 8Pa for 4 to 6 hours, and obtain a pre-modified conjugated porous polymer; the impregnation solution is prepared by mixing 2,2-dihydroxymethylpropionic acid and p-toluenesulfonic acid in a mass ratio of 100:1 to 100:2; (3) 10-undecenylamine, pre-modified conjugated porous polymer, anhydrous ethanol and toluene were mixed uniformly in a mass ratio of 1:8:40:40 to 1:10:50:50, and a catalyst of 0.01 to 0.03 times the mass of 10-undecenylamine was added. The mixture was subjected to ultrasonic reaction at 60 to 70°C and 30 to 40 kHz for 6 to 8 hours. The mixture was cooled to room temperature and filtered, washed with anhydrous ethanol for 3 to 5 times, and dried at -1 to -10°C and 1 to 10 Pa for 6 to 8 hours. h, then immersed in a monoiodomethane solution, stirred at 30~40℃ and 500~800r / min for 4~6h, then heated to 50~60℃ and maintained for 20~30min, cooled to 1~5℃ and filtered, rinsed with 1~5℃ 8% sodium bicarbonate solution for 3~5min, then washed with 1~5℃ pure water for 3~5 times, dried at -10~-1℃, 1~10Pa for 6~8h, to obtain a modified conjugated porous polymer; (4) The copolymer, 1,2,4,5-tetrakis(4-carboxyphenyl)benzene, N,N-dimethylacetamide, anhydrous ethanol and pure water were mixed uniformly in a mass ratio of 1:3:8:6:4 to 1:5:10:8:6, and then 0.02 to 0.03 times the mass of the copolymer of dicyclohexylcarbodiimide and 0.02 to 0.03 times the mass of the copolymer of 1-hydroxybenzotriazole were added, and the mixture was stirred at 40 to 50°C and 500 to 800 r / min for 10 to 12 h, and then allowed to stand at 20 to 30°C and 1 to 2 kPa for 6 to 8 h, filtered and washed with anhydrous ethanol. The copolymer is prepared by washing with anhydrous ethanol for 3 to 5 times, and drying at -10 to -1°C and 1 to 10Pa for 6 to 8 hours to obtain a modified copolymer; the preparation method of the copolymer is as follows: p-aminostyrene, propylene, anhydrous ethanol and toluene are uniformly mixed in a mass ratio of 1:1:6:6 to 1:1:8:8, and a catalyst of 0.01 to 0.03 times the mass of p-aminostyrene is added, and the mixture is placed in a reaction kettle, reacted at 60 to 70°C for 6 to 8 hours, filtered after cooling to room temperature, and washed with anhydrous ethanol for 3 to 5 times, and dried at -1 to -10°C and 1 to 10Pa for 6 to 8 hours to obtain the copolymer; (5) Polypropylene alcohol, modified conjugated porous polymer, modified copolymer, tetrahydrofuran, N,N-dimethylformamide, polyethylene glycol, and 50% ethanol by mass fraction were mixed in a mass ratio of 3:1:1:6:6:0.1:4-5:1:1:8:8:0.2:5, and electrospun at a spinning voltage of 15-20 kV, a spinneret aperture of 0.7 mm, a receiving distance of 15-20 cm, an ambient temperature of 10-20 °C, and allowed to stand at 50-60 °C, 1-2 kPa for 4-6 h to obtain fibers; the fibers were twisted to 70-90 D, and then formed into fibers with a gram weight of 80-90 g / m by a weaving machine. 2 Anti-mildew quick-drying towel fabric.

2. The method for preparing a mildew-proof quick-drying towel fabric according to claim 1, characterized in that: The catalyst in steps (3) and (4) is prepared by uniformly mixing triethylaluminum and titanium tetrachloride in a mass ratio of 1:1 to 3:

5.

3. The method for preparing a mildew-proof quick-drying towel fabric according to claim 1, characterized in that: The monoiodomethane solution in step (3) is prepared by uniformly mixing monoiodomethane, a sodium hydroxide solution having a mass fraction of 8 to 10%, and sodium iodide in a mass ratio of 5:3:0.003 to 5:4:0.005.

Citation Information

Patent Citations

  • Moisture-absorption quick-dry antibacterial fabric and preparation method thereof

    CN114250541A